Analisis Kinerja Algoritma YOLO dalam Penghitungan Benih Udang - Siska Armalivia; Muhammad Abdillah Rahmat; Thiara Tri Funny Manguma; Rahmawati (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2024)
The two main processes in shrimp cultivation are filling and enlargement. The counting of shrimp seeds is part of the filling activity. However, the counting of shrimp after larvae is still done manually, which means taking the shrimp and counting them manually, which is time-consuming and often results in human error. This research proposes a You Only Look Once (YOLO) method to automatically calculate the number of shrimp larvae. The YOLO method is a deep learning model that can detect an object with high speed and accuracy, even under less ideal lighting conditions. In this study, images of objects were taken using a camera placed on top of a white container containing 2 cm of water and photographed with a backlight system to avoid the reflection of light from inside the water. Testing is done by comparing system calculations and manual calculations. The results showed that the system not only detected larvae but also counted the number of shrimp larvae as well as the mAP validation value on the final model built with YOLO, which was 96.83% It also produced an average accuracy with 30 training data of 76.48%.